Non-thermal plasma-enhanced reverse water-gas shift reaction over hydroxyapatite-supported Ni catalyst: Effect of severe process conditions - Farbod Farzi; Erwan Baudillon; Romain Kersaudy; Inès Esma Achouri (Journal of CO2 Utilization)
CO2 hydrogenation to carbon monoxide and water (Reverse Water Gas Shift reaction) is a promising way to valorize CO2. It is the preliminary step in the methanol and Fischer-Tropsch synthesis processes. However, the thermodynamic barrier has limited the industrial scale-up of this process, and thus, the need for a proper catalyst formulation and reactor configuration is still ongoing. In this paper, we studied the catalytic performance of a hydroxyapatite-supported nickel-zirconia catalyst in a microwave plasma reactor for the CO2 hydrogenation to carbon monoxide. A 10 wt% Ni- ZrO2/HAp catalyst was prepared by the wetness impregnation method, dried at 180 °C for 18 h and calcined at 500°C for 3 h. The influence of the H2/CO2 molar ratio, power, and GHSV on CO2 conversion and CO selectivity was studied. In the selected range of GHSV, it did not influence the output parameters. Moreover, CO selectivity remained in the range of 98–100 % in all experiments. The highest carbon yield was 83 % under H2/CO2 to 2:1, Power= 2.25 kW, and GHSV= 80,000 mL.gr−1.hr−1 while maintaining 9 % energy efficiency. The high CO2 conversion is justified due to the interaction of a basic catalyst with the CO2 (weak acid) which facilitated the CO2 reduction to CO as well as the microwave discharge reactor, whose temperature characteristics meet the requirement of the RWGS reaction. In addition, an energy efficiency equal to 28 % was observed under H2/CO2 to 1:1, Power= 0.8 kW, and GHSV= 120,000 mL.gr−1.hr−1. To the best of our knowledge, these values have never been attained before. In this study, we proposed a novel catalyst formulation for the CO2 hydrogenation reaction, tested a microwave discharge for the reaction, and operated at very high GHSV levels, which are suitable for industrial production.